The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1128/spectrum.00914-22
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Distribution of SARS-CoV-2 Lineages across Multiple Rounds of Pandemic Waves in West Bengal, the Gateway of East and North-East States of India

Abstract: Multiple waves of infection were observed in many states in India during the coronavirus disease 2019 (COVID19) pandemic. Fine-scale evolution of major SARS-CoV-2 lineages and sublineages during four wave-window categories: Pre-Wave 1, Wave 1, Pre-Wave 2, and Wave 2 in four major states of India: Delhi (North), Maharashtra (West), Karnataka (South), and West Bengal (East) was studied using large-scale virus genome sequencing data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Soon after its emergence, India started to experience a rapid surge in cases of coronavirus disease 2019 (COVID-19) from early March to July, 2021, garnering global attention [2]. Genomic investigations indicated that the Delta variant nearly completely replaced previously circulating variants, including B.1.1.7 (Alpha), B.1.617.1 (Kappa), and others [3][4][5]. Even globally, the Delta variant had become dominant by mid-2021 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Soon after its emergence, India started to experience a rapid surge in cases of coronavirus disease 2019 (COVID-19) from early March to July, 2021, garnering global attention [2]. Genomic investigations indicated that the Delta variant nearly completely replaced previously circulating variants, including B.1.1.7 (Alpha), B.1.617.1 (Kappa), and others [3][4][5]. Even globally, the Delta variant had become dominant by mid-2021 [6].…”
Section: Introductionmentioning
confidence: 99%